SP0033 The eular campaign "dont delay connect today" and how organisations can get involved. (15th June 2017) - Church, J
Abstract : Arthritis is a chronic disease with multiple co-morbidities. With the development of powerful biologic drugs, improvements in care pathways for patients and very effective self-management interventions, early diagnosis and intervention can lead to significant improvements in liefstyle, physical movement, incerased well-being and work force participation. Despite its significant impact on the population and the cost to the economy, Arthritis still remains an underfunded subspecialty within the health systems and one that is shrouded in public myth. The EULAR campaign "Done Delay, Connect Today", aims to promote early intervention by encouraging those with typical symptoms to take action and consult their doctor at the earliest possible opportunity. The campaign which will be adopted and executted across all PARE members also aims to dispel the myths and educate the public about the seriosness of arthritis and the need to taek action. Disclosure of Interest: None declared